The political economy of sports television - Kunz, William M., 1961- (London ; New York : Routledge, 2020)
"Drawing from theories of the political economy of communication, this book offers readers a comprehensive data-rich assessment of contemporary sports television and its evolution. Providing an in-depth look at the ownership and regulation of sports television in the United States, William M. Kunz analyzes a range of platforms, networks, and sports, with particular focus on the way ownership has become concentrated in five conglomerates: AT&T, CBS, Comcast, Disney and Fox. The end result of years of media consolidation is that broadcast networks are now married to cable and streaming services under a single conglomerate, which has implications for the cost of contracts and the negotiation of distribution deals. Examining multiple platforms, networks and sports in an all-inclusive manner, this volume documents the evolution and current state of affairs of sports television. With historic and current data on rights fees for sports television leagues and events as well as carriage fees and subscription levels for sports-related cable and satellite services, this comparative study offers critical information for students and scholars conducting research on sports television"--
Conglomeration of sports television networks & services -- National multi-sport networks -- National single sport, league & conference networks -- Regional sports networks -- Streaming & out-of-market services.
OCLC-licensed vendor bibliographic record.
Keywords: Television broadcasting of sports -- Economic aspects -- United States; Television broadcasting -- Ownership -- United States; Television broadcasting of sports -- Political aspects -- United States; Television broadcasting policy -- United States; SOCIAL SCIENCE / Media Studies